METHODOLOGY IN ART - Karimov Abduraxmon Qodirovich; Zulfiyev Rashid Ne’matovich (Journals Park Publishing, 2022)
The article is devoted to the description of the normative "framework" for the use of methodology in art studies, unfolding in a disciplinary cognitive situation.